Dynamic process safety assessment by mapping ALOHA simulation into Bow-tie analysis: application to distillation column in production of acetic acid / Aiman Alif Bashari - Bashari, Aiman Alif (2023)
The production of acetic acid has been found to have several key issues that could result in serious accidents if not addressed. The distillation column has been identified as the main point of concern. This project aims to analyse the hazards posed by chemicals passing through the heat exchanger by conducting risk analysis during the preliminary stage of chemical production site design. Two risk analysis methods will be used which is Bow tie analysis and Areal Locations of Hazardous Atmospheres (ALOHA) modelling software. Bow tie analysis provides insight into the root causes of accidents and potential consequences but lacks detail. The bow tie analysis also uses Inherent Safer Design (ISD) principles, such as minimizing, moderating, simplifying, and substituting, to create mitigative barriers. ALOHA modelling software provides a more detailed analysis of consequences, showing the extent of the threat zone. The results from the ALOHA modelling software indicate that the most hazardous chemical from the heat exchanger in the production of acetic acid is acetic acid itself. The threat zone is shown to include scenarios involving non-burning tanks and toxic vapor clouds. By utilizing both Bow tie analysis and ALOHA modelling software, the most effective risk assessment can be conducted and the current hazards can be reduced.